(untitled) (Journal of Chemical Engineering, 2010)
The combustion performance and emissions of liquid fuels are mainly influenced by the atomization of the liquid fuel, the motion and evaporation of the fuel droplets and mixing of fuel and air. A reliable description and simulation of spray combustion requires a detailed understanding of droplet ignition and combustion. Recently, it has become apparent that an understanding of the mechanisms related to spray combustion is the key to the development of non-polluting and high performance devices. In this study liquid droplets of Toluene is taken into consideration and their burning characteristics are investigated for different combustor geometries and droplet sizes. Non-adiabatic presumed probability density function (PPDF) model is used with high Reynolds number k-ε model. Droplet breakups are handled with Reitz- Diwakar model. Preliminary investigation shows that droplet size, inlet pattern and oxidizer temperature have profound effect on combustion temperature distribution and pollutant formation. Journal of Chemical Engineering Vol.ChE 24 2006 14-18